Individual participant data systematic reviews with meta-analyses of psychotherapies for borderline personality disorder. Issue 6 (21st June 2021) - Storebø, Ole Jakob; Ribeiro, Johanne Pereira; Kongerslev, Mickey T; Stoffers-Winterling, Jutta; Sedoc Jørgensen, Mie; Lieb, Klaus; Bateman, Anthony; Kirubakaran, Richard; Dérian, Nicolas; Karyotaki, Eirini; Cuijpers, Pim; Simonsen, Erik
Abstract : Introduction: The heterogeneity in people with borderline personality disorder (BPD) and the range of specialised psychotherapies means that people with certain BPD characteristics might benefit more or less from different types of psychotherapy. Identifying moderating characteristics of individuals is a key to refine and tailor standard treatments so they match the specificities of the individual participant. The objective of this is to improve the quality of care and the individual outcomes. We will do so by performing three systematic reviews with meta-analyses of individual participant data (IPD). The aim of these reviews is to investigate potential predictors and moderating patient characteristics on treatment outcomes for patients with BPD. Methods and analysis: We performed comprehensive searches in 22 databases and trial registries up to October 6th 2020. These will be updated with a top-up search up until June 2021. Our primary meta-analytic method will be the one-stage random-effects approach. To identify predictors, we will use the one-stage model that accounts for interaction between covariates and treatment allocation. Heterogeneity in case-mix will be assessed with a membership model based on a multinomial logistic regression where study membership is the outcome. A random-effects meta-analysis is chosen to account for expected levels of heterogeneity. Ethics and dissemination: The statistical analyses will be conducted on anonymised data that have already been approved by the respective ethical committees that originally assessed the included trials. The three IPD reviews will be published in high-impact factor journals and their results will be presented at international conferences and national seminars. PROSPERO registration number: CRD42021210688.